The Qiroati Method as a Teaching Medium for Qur’anic Learning among Students - Mariana, Mariana; Nirwana, Evi Selva; Kurniawan, Kurniawan (Indonesian Journal of Research in Islamic Studies, 2025)
Objective: Teaching the Qur'an in elementary schools requires effective methods so that students are not only able to read the Qur'an, but also understand the correct reading rules (tartil and tajwid). One method that is widely used in Islamic schools is the Qiroati method. Purpose: This study aims to determine the effectiveness of the Qiroati method in teaching the Qur'an at SDI Al-Azhar 51 in Bengkulu City. Method: This study uses a descriptive qualitative approach. The research subjects included the principal, Qiroati teachers, and Qiroati assistant teachers. Data were collected through observation, interviews, and documentation. Data validity was tested using source triangulation, method triangulation, and theory triangulation. Results: The Qiroati method has been implemented effectively in accordance with learning procedures; however, its implementation has not been entirely optimal. This is due to limited learning time during the pandemic and a shortage of educators, especially those competent in the Qiroati method. Nevertheless, the Qiroati method is considered adequate because it is practical, easy to understand, systematic, and suitable for step-by-step learning. Students were able to recite clearly, follow the rules of tartil, and understand basic tajwid well. Conclusion: The Qiroati method is effective for teaching the Qur'an at SDI Al-Azhar 51 in Bengkulu City, although it still requires improvement in terms of learning duration and the availability of competent educators. Contribution: This study provides input for schools and educators to enhance the quality of Al-Qur'an learning by optimizing the Qiroati method, particularly in terms of learning time planning, teacher training, and a continuous evaluation system.